(untitled) (Al-Academy, 2024)
Since ancient times, man has been keen to provide means of comfort and safety in his dwelling and the surrounding environment around that space by observing and harnessing them for his benefit within his dwelling or the space he uses. Surrounded by atmospheric, climatic, psychological and behavioral conditions and knowing the developments that occur in technology for the purpose of benefiting from them in adapting the environment that we use and we strive to make it ideal. Therefore, we must know the mechanisms and systems that bring us to this peak and try to achieve them or look at them for the purpose of using them in the correct scientific ways that provide us with psychological comfort Health, material and economic, through which we will address the mechanisms of environmental adaptation in the interior spaces of the gymnasiums. Their compatibility for gym users, the research also focused on presenting a study called for the need to improve the health and environmental level and knowledge of the mechanisms of environmental adaptation. It has the ability to detect environmental control systems and the extent to which internal space users adapt to them.As for the second chapter, it contained the details of the theoretical framework for the research and was divided into two chapters. The first chapter presented the environmental control systems in gymnasiums, and the second chapter presented theoretical interpretations of the concept of environment and adaptation. The methodology of the research adopted in the third chapter, which included the research procedures and methodology, so we relied on the descriptive approach of the total research community according to the reasons revealed in the analysis through the indicators of the theoretical framework, while the fourth chapter included a review of the results from which the theoretical material was summarized for the second chapter and from Most notably, the most important basics in achieving adaptation is that the space is independent and has a unit of idea and design of its own according to approved standards. For the purpose of achieving success, the designer must be aware of the nature of the region and its climate to control the adaptive, environmental and health systems, as well as knowing the amount of air, humidity and standard temperatures to achieve The best results